Horpadások a karosszérián – felelős társaságirányítási kérdések az elmúlt időszak autóipari botrányainak tükrében - Ferencz , Barnabás (Debreceni Jogi Műhely, 2016)
The aim of the article is to examine the key corporate governance issues in light of the recent scandals in the automotive industry. The article explores the underlying reasons which culminated in the events of the General Motors ignition switch scandal, and Volkswagen’s "Dieselgate". While these two events may seem unrelated at the first glance, however, the facts show that similar problems led to these scandals, most of which were deeply rooted in the corporate culture. Factors, such as the lack of clear and honest communication and the willingness to bend the rules show that the principles of corporate governance were not put in practice within these corporations. The author believes that by taking corporate governance seriously the scandals could have been entirely preventable.